CORPORATE CULTURE AS A DETERMINANT OF THE EFFICIENCY OF INTERNAL COMMUNICATIONS IN THE SYSTEM OF STRATEGIC MANAGEMENT OF AN ENTERPRISE - Громова, Олена (SWorldJournal, 2025)
The article examines the relationship between corporate culture and the effectiveness of internal communications within the enterprise’s strategic management system. It reveals the role of culture as a determinant of organizational resilience, adaptabilit